In Vitro Cytotoxic Activity of Methanol Extracts of Selected Medicinal Plants Traditionally Used in Mexico against Human Hepatocellular Carcinoma - Elizondo Luévano, Joel Horacio; Gómez Flores, Ricardo Alberto; Verde Star, María Julia; Tamez Guerra, Patricia; Romo Sáenz, César Iván; Chávez Montes, Abelardo; Rodríguez Garza, Nancy Edith; Quintanilla Licea, Ramiro (Multidisciplinary Digital Publishing Institute, 2022)
Medicinal plants are traditionally used in Mexico to treat diseases such as cancer. The present study aimed to evaluate the cytotoxic, antioxidant, and anti-hemolytic activity of 15 plants of ethnopharmacological use in Mexico. For this, plant methanol extracts were prepared by the Soxhlet method, after which their cytotoxic activity was evaluated against human hepatocellular carcinoma (HEP-G2) and monkey kidney epithelial (Vero) cells by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction colorimetric assay. The selectivity index (SI) of each extract was then determined by the IC50 ratio of normal to tumor cells. We showed that Ruta chalepensis extract possessed an IC50 of 1.79 µg/mL and 522.08 µg/mL against HEP-G2 and Vero cells, respectively, resulting in an SI of 291.50. Furthermore, antioxidant activity was evaluated by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging technique, where the best antioxidant potential was shown by the Heterotheca inuloides extract (IC50 = 19.24 µg/mL). Furthermore, the hemolytic potential was determined against human erythrocytes, which showed that the extracts with the highest anti-hemolytic activity were Smilax aspera (IC50 = 4.41 µg/mL) and Amphipterygium adstringens (IC50 = 5.35 µg/mL). In conclusion, we observed that R. chalepensis methanol extract possesses cytotoxic activity against HEP-G2 cells, without affecting non-tumorigenic Vero cells. Our results indicated the antitumor potential of medicinal plants used in Mexico.